Preliminary inventory of the records of the Bureau of Indian Affairs : (Record group 75) - Hill, Edward E. (National Archives preliminary inventories ;, 1965)
Records of the Bureau of Indian Affairs compiled by Edward E. Hill for the National Archives of the United States. Includes records of related and predecessor agencies.